ANALYSIS OF THE ROLE OF SOCIAL MEDIA AND PACKAGING ON SALES OF TEMPOYAK MAK SYALU UMKM IN PALEMBANG CITY - Iga Apria; Desti Destiansari Istinabiyah; Dwi Mei Rita Sari; Kamilia Syaputra (STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the influence of social media and packaging on the sales performance of the Tempoyak Mak Syalu MSME in Palembang, which faces marketing challenges in the digital era and increasing competition among local culinary products. This research employs a quantitative approach using a descriptive–verificative design, involving 100 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability tests, t-test, F-test, and multiple linear regression analysis. The results reveal that both social media and packaging significantly influence sales, both partially and simultaneously. Social media effectively expands promotional reach, enhances consumer interaction, and strengthens product image. Meanwhile, appealing and informative packaging contributes to perceived product quality and consumer purchase intentions. The discussion reinforces previous findings stating that the combination of digital marketing and packaging innovation enhances MSME competitiveness. This study concludes that integrating both strategies is essential for improving the sales of tempoyak products and provides practical implications for MSMEs in optimizing marketing strategies within the digital landscape.